2019
DOI: 10.3399/bjgp19x704117
|View full text |Cite|
|
Sign up to set email alerts
|

Skill-mix change in general practice: a qualitative comparison of three ‘new’ non-medical roles in English primary care

Abstract: BackgroundGeneral practice is currently facing a significant workforce challenge. Changing the general practice skill mix by introducing new non-medical roles is recommended as one solution; the literature highlights that organisational and/or operational difficulties are associated with skill-mix changes.AimTo compare how three non-medical roles were being established in general practice, understand common implementation barriers, and identify measurable impacts or unintended consequences.Design and settingIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 29 publications
3
58
1
1
Order By: Relevance
“…The data from this project suggests that, in the geographical region where the evaluation was carried out, there appeared to be a widespread acceptance of, and appreciation for, the ACP role. This is in contrast to many studies that highlight professional boundary tensions and role conflicts (both between GPs and ACPs as well as between practice nurses and ACPs) [ 38 , 39 , 57 ]. A few respondents noted some initial apprehension from GPs about the ACP role, but this was represented as a historical issue.…”
Section: Discussioncontrasting
confidence: 66%
“…The data from this project suggests that, in the geographical region where the evaluation was carried out, there appeared to be a widespread acceptance of, and appreciation for, the ACP role. This is in contrast to many studies that highlight professional boundary tensions and role conflicts (both between GPs and ACPs as well as between practice nurses and ACPs) [ 38 , 39 , 57 ]. A few respondents noted some initial apprehension from GPs about the ACP role, but this was represented as a historical issue.…”
Section: Discussioncontrasting
confidence: 66%
“… 42–45 However, resonating with other recent research, we also identified frustrations and lack of clarity around pharmacists’ roles, with limited opportunity to conduct face to face medication reviews. 46 47 …”
Section: Discussionmentioning
confidence: 99%
“…Often a cause of confusion among patients and HCPs alike, many authors report that the historic ambiguity of ACP role and scope of practice is finally becoming clearer with the introduction of a national framework and definition (Pearce & Breen, 2018). There is a consistent opinion that the HEE framework is a much-needed approach to understand, recognise, and standardise ACP, which is often cited as a challenge when implementing such a role (Wright et al, 2018;Nelson et al, 2019). Considering past national healthcare policies highlighted the same issues as today, these developments may be the positive step towards the greater success of an ACP role.…”
Section: Recognition Of Acpmentioning
confidence: 99%